Obesity-Mediated Immune Modulation: One Step Forward, (Th)2 Steps Back - Schmidt, Viviane; Hogan, Andrew E.; Fallon, Padraic G.; Schwartz, Christian (Frontiers in Immunology, 2022)
Over the past decades, the relationship between the immune system and metabolism have become a major research focus. In this arena of immunometabolism the capacity of adipose tissue to secrete immunomodulatory molecules, including adipokines, within the underlying low-grade inflammation during obesity brought attention to the impact obesity has on the immune system. Adipokines, such as leptin and adiponectin, influence T cell differentiation into different T helper subsets and their activation during immune responses. Furthermore, within the cellular milieu of adipose tissue nutrient availability regulates differentiation and activation of T cells and changes in cellular metabolic pathways. Upon activation, T cells shift from oxidative phosphorylation to oxidative glycolysis, while the differential signaling of the kinase mammalian target of rapamycin (mTOR) and the nuclear receptor PPARγ, amongst others, drive the subsequent T cell differentiation. While the mechanisms leading to a shift from the typical type 2-dominated milieu in lean people to a Th1-biased pro-inflammatory environment during obesity are the subject of extensive research, insights on its impact on peripheral Th2-dominated immune responses become more evident. In this review, we will summarize recent findings of how Th2 cells are metabolically regulated during obesity and malnutrition, and how these states affect local and systemic Th2-biased immune responses.